Necrotising enterocolitis in the very low birthweight infant: expressed breast milk feeding compared with parenteral feeding. Issue 4 (April 1982) - Eyal, F; Sagi, E; Arad, I; Avital, A
Abstract : The incidence of necrotising enterocolitis (NEC) in very low birthweight infants (VLBW less than or equal to 1500 g) was reduced by the delayed onset of enteral feeding. Eight (18%) out of 44 VLBW infants who were in hospital during the first year of the study developed NEC. During the next 12 months 85 similar infants were initially fed by parenteral nutrition only, and then from age 14-21 days with infant formula. During the second year only 3 (3%) patients developed NEC. There were no other relevant changes in management. Throughout the entire study, the onset of NEC in each infant in whom it occurred was after the start of enteral feeding. We recommend avoiding enteral feeding in VLBW infants during the period that they are particularly vulnerable–namely the first 2 or 3 weeks of life.